Food and agricultural wastes-derived biochars in combination with mineral fertilizer as sustainable soil amendments to enhance soil microbiological activity, nutrient cycling and crop production - Mustafa, Adnan; Brtnicky, Martin; Hammerschmiedt, Tereza; Kucerik, Jiri; Kintl, Antonin; Chorazy, Tomas; Naveed, Muhammad; Skarpa, Petr; Baltazar, Tivadar; Malicek, Ondrej; Holatko, Jiri (Frontiers in Plant Science, 2022)
The ever-increasing human population associated with high rate of waste generation may pose serious threats to soil ecosystem. Nevertheless, conversion of agricultural and food wastes to biochar has been shown as a beneficial approach in sustainable soil management. However, our understanding on how integration of biochar obtained from different wastes and mineral fertilizers impact soil microbiological indicators is limited. Therefore, in the present study the effects of agricultural (AB) and food waste derived (FWB) biochars with and without mineral fertilizer (MF) on crop growth and soil health indicators were compared in a pot experiment. In particular, the impacts of applied amendments on soil microbiological health indicators those related to microbial extracellular (C, N and P acquiring) enzymes, soil basal as well as different substrate induced respirations along with crop’s agronomic performance were explored. The results showed that compared to the control, the amendment with AB combined with MF enhanced the crop growth as revealed by higher above and below ground biomass accumulation. Moreover, both the biochars (FWB and AB) modified soil chemical properties (pH and electric conductivity) in the presence or absence of MF as compared to control. However, with the sole application of MF was most influential strategy to improve soil basal and arginin-induced respiration as well as most of the soil extracellular enzymes, those related to C, N and P cycling. Use of FWB resulted in enhanced urease activity. This suggested the role of MF and FWB in nutrient cycling and plant nutrition. Thus, integration of biochar and mineral fertilizers is recommended as an efficient and climate smart package for sustainable soil management and crop production.